DOMS-associated changes in ankle and knee joint dynamics during running - Dutto, D. J.; Braun, W. A. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The purpose of this study was to determine whether leg mechanics change due to DOMS by examining ankle and knee joint kinematics and stiffness before and after a down hill run. Methods: Sagittal plane kinematics were recorded with high-speed (120 Hz) video at a speed representing 75% of [latin capital V with dot above]O2peak of nine well-trained male runners before (RE1) and 48 h after (RE2) a 30-min downhill run. From the recorded video, 10-12 consecutive strides were digitized, and the following variables were calculated for each stride: ankle and knee range of motion (ROM), ankle and knee peak angular velocity, ankle and knee stiffness, and leg vertical stiffness. A repeated measures ANOVA was calculated for each variable ([alpha] = 0.05). Results: Both knee and ankle ROM during stance decreased with DOMS, but otherwise there were few changes in ankle mechanics with DOMS. Knee stiffness tended to increase during the early portion of stance (from initial stance to maximum angular velocity of flexion) with DOMS, immediately followed by a decrease (to maximum knee flexion) in stiffness. Changes in knee stiffness caused vertical leg stiffness to increase for the initial portion of stance with DOMS. Conclusion: Knee mechanics changed such that the knee stiffness increased at initial stance, resulting in an increase in vertical leg stiffness. This change in knee stiffness possibly serves as a protective mechanism to prevent further damage or pain in the knee extensor musculature.